Endovascular Treatment of Basilar Artery Aneurysms Associated with Distal Fenestration: A Case Report - Juszkat, R. (Centauro S.r.l., 2009)
Segmental non-fusion of the basilar artery results from failed fusion of the neural arteries and from regression of the bridging arteries that connect the longitudinal arteries. This condition is associated with aneurysm formation in 7% of cases. Distally unfused arteries with associated aneurysms are very rare. We report on a case of successful endovascular treatment of an aneurysm of the distally unfused basilar trunk.